On Harmonically (p,h,m)-Preinvex Functions - Shan-He Wu; Imran Abbas Baloch; İmdat İşcan (Journal of Function Spaces)
We define a new generalized class of harmonically preinvex functions named harmonically (p,h,m)-preinvex functions, which includes harmonic (p,h)-preinvex functions, harmonic p-preinvex functions, harmonic h-preinvex functions, and m-convex functions as special cases. We also investigate the properties and characterizations of harmonically (p,h,m)-preinvex functions. Finally, we establish some integral inequalities to show the applications of harmonically (p,h,m)-preinvex functions.